A game theoretic study on CSR and government intervention for sustainable production - Fernandez, Katherine Ann J. (Animo Repository, 2021)
This study uses a game theoretic approach to assess how the government can influence firms’ CSR investment and production decisions to enhance social welfare, considering the negative externalities brought by unsustainable production and positive externalities brought by CSR investments. Using a Stackelberg duopoly as a base model and lump sum tax as the government’s decision variable, this study finds that when the government chooses not to intervene, it results in greater environmental damage as firms will underinvest in CSR and overproduce in quantity to achieve profit maximization. As such, the model extends to the assumption that the government acts as a benevolent dictator to model how firms will act under a regulated environment to achieve the Pareto Optimal Outcome. Ultimately, this study shows that firms have to be placed under a regulated environment so as to prevent them from exploiting resources and damaging the environment, thereby negatively affecting societal welfare.